Characterization of the mitochondrial genome of Tetrameres grusi and insights into the phylogeny of Spirurina. (April 2022) - Gao, Jun-Feng; Mao, Rui-Feng; Li, Ye; Sun, Yun-Yi; Gao, Zhong-Yan; Zhang, Xian-Guang; Jin, Zhen-Hua; An, Qi; Zhang, Zhong-Huai; Zhang, Ai-Hui; Wei, Wei; Lan, Zhuo; et al.
Abstract: Tetrameres grusi is a significant parasitic nematode of cranes that is classified into suborder Spirurina. However, for more than a century, this classification has been controversial. Mitochondrial genomes are valuable resources for parasite taxonomy, population genetics and systematics studies. Here, the mitochondrial genome of T. grusi was determined and subsequently compared with those from Spirurina species using concatenated datasets of amino acid sequences predicted from mitochondrial protein-coding genes. The complete mitochondrial genome of T. grusi is circular with 13, 709 bp, and it contains 12 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes and one non-coding region. All of the protein-coding genes are transcribed in the same direction. There were 18 intergenic spacers of 1–44 bp, and six locations with gene overlaps, ranging from 1 bp to 28 bp, in the mitochondrial genome of T. grusi . The AT content of this mitochondrial genome was 71.56%. This was similar to mitochondrial genomes of other Spirurina species, which also exhibited strong AT content bias, not only in the nucleotide composition but also in codon usage. The sequenced mitogenomes of the 25 Spirurina nematodes showed three classes of gene arrangements based on the 12 protein-coding genes, and the gene arrangement of the T. grusi mitochondrial genome belonged to the Class I. Phylogenetic analyses using mitochondrial genomes of 25 Spirurina nematodes revealed that T. grusi (Habronematoidea) was closer to Gongylonema pulchrum (Spiruroidea) than Spirocerca lupi (Thelazioidea). The availability of the complete mitochondrial genome sequence of T. grusi provides new and useful genetic markers for further studies on Spirurina nematodes. Graphical abstract: Image 1 Highlights: The complete mitochondrial genome of Tetrameres grusi is reported for the first time. Spirurina nematodes showed three classes gene arrangements based on the 12 PCGs, and Tetrameres grusi belonged to Class I. Our phylogenetic analyses revealed Tetrameres grusi was more closely related to Gongylonema pulchrum than Spirocerca lupi .